2017
DOI: 10.1007/s40653-017-0177-5
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Caregiver Factors Predicting Participation in Trauma-Focused Cognitive Behavioral Therapy

Abstract: This study examined patterns of caregiver factors associated with Trauma-Focused Cognitive Behavioral Therapy (TF-CBT) utilization among trauma-exposed youth. This study included 41 caregivers (caregiver age M = 36.1, SD = 9.88; 93% African American) of youth referred for TF-CBT, following a substantiated forensic assessment of youth trauma exposure. Prior to enrolling in TF-CBT, caregivers reported on measures for parenting stress, attitudes towards treatment, functional impairment, caregiver mental health di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 68 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…Notably, research has shown that using targeted brief intervention strategies to address perceptual challenges for identified stakeholders can effectively improve initial and ongoing engagement to support retention in therapeutic services (Kim et al, 2012;Lai et., 2017;McKay et al, 2001). These strategies include using the first telephone contact and the first visit to involve caregivers and identify their treatment priorities (McKay & Bannon, 2004).…”
Section: Therapeutic Engagementmentioning
confidence: 99%
“…Notably, research has shown that using targeted brief intervention strategies to address perceptual challenges for identified stakeholders can effectively improve initial and ongoing engagement to support retention in therapeutic services (Kim et al, 2012;Lai et., 2017;McKay et al, 2001). These strategies include using the first telephone contact and the first visit to involve caregivers and identify their treatment priorities (McKay & Bannon, 2004).…”
Section: Therapeutic Engagementmentioning
confidence: 99%